A mechanistic understanding of the effect of lime and compost on soil cadmium availability in cacao farms - Wiersma, Wietse; Favaro, Anna; Comans, Rob N.J.; Pulleman, Mirjam Margreet; Groenenberg, Jan E. (American Chemical Society, 2025)
To develop soil amendments that effectively lower cadmium uptake by food crops, a mechanistic understanding is needed of the factors influencing Cd availability in amended soils. This insight is highly relevant in the context of food safety regulations affecting the cacao sector in Latin America. Geochemical multisurface models (MSMs) can be used to generate such knowledge, yet their potential for this purpose remains underexplored. We performed a laboratory incubation experiment with five different soils from cacao farms, which we amended with four types of compost at a rate equivalent to 30 t ha–1, with or without the addition of 1.75 t ha–1 lime (CaCO3). The MSM showed a high ability to capture proportional changes in Cd availability enacted by the treatments based on changes in soil solution properties measured with a low-salt extraction (0.001 M Ca(NO3)2) or rhizon samplers. In general, the effect of compost and lime on Cd geochemistry was highly soil- and compost-specific, and pH (change) was found to be the main driver of Cd availability. Additionally, we used diffusive gradient in thin film (DGT) devices to gain insight into Cd availability over time. Despite being a minor adsorption surface for Cd compared to organic matter, the MSM-assisted interpretation of DGT results suggests an important role for clay particles in Cd buffering. Our work helps explain the often ambiguous effects of soil amendments on Cd uptake by plants and positions MSMs as capable tools for the design of management strategies aimed at mitigating Cd in cacao.